Mapping Research Trends On Education Management In Elementary Schools: A Bibliometric Analysis Using Scopus Database - Akrom, Abdul Hayyi; Ziadi, M. Rohman; Jehwae, Phaosan (BADA'A: Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the development of elementary school education management research from 2003 to 2025 using bibliometric methods. A total of 934 Scopus-indexed documents were analyzed with Bibliometrix and RStudio to identify publication trends, thematic developments, and global collaboration patterns. The results show rapid growth in this field, with an annual growth rate of 14.56%, alongside increasing topic diversity, including school leadership, teacher development, parental involvement, school improvement, and primary education. Thematic analysis indicates a shift from traditional concerns such as school administration and leadership toward newer issues, including inclusive education, student wellbeing, and academic achievement. Leadership remains a central theme, but it is now more interconnected with broader educational issues. Core themes such as primary education and student learning continue to shape the field, while mental health and psychology are emerging as new interdisciplinary topics. The study also highlights unequal global research productivity. The United States, United Kingdom, Australia, South Africa, and Turkey dominate publication output, while international collaboration remains concentrated in anglophone networks. Overall, this study provides a concise overview of the field’s intellectual growth, main thematic trends, and global research dynamics, offering useful insights for researchers, educators, and policymakers